The generation who would - Abrahams, Aneeqa (WritingThreeSixty, 2020)
The position of young people in politics is often overlooked and missing from the conversation however, this is of no indication that they are not interested in politics or the shaping of the political climate in their respective countries (Jennings-Edquist, 2019). The theorisation of the space young people occupy in the political sphere has noted that expanding the field of who has political footing and power to make social change has led to viewing the lived experiences of youth in a different light and recognising them as active beings who have voice instead of ‘future becomings’ who will eventually have voice (Pauliina & Jouni, 2013). Research has also indicated that young people are more likely to use alternative modes to obtain and engage with political content and authorities (social media, protests, rallies) while being more critical about the political parties they vote for if they decide to vote (Newham & Roberts, 2019; Jennings-Edquist, 2019).